Climate variability and vulnerability to poverty in Nicaragua. Issue 3 (3rd July 2018) - Herrera, Carlos; Ruben, Ruerd; Dijkstra, Geske
ABSTRACT: This study considers the effect of climate variability on vulnerability to poverty in Nicaragua. It discusses how such vulnerability could be measured and which heterogeneous effects can be expected. A multilevel empirical framework is applied, linking per capita consumption to household, regional and climate characteristics. Results confirm a negative effect of climate variability on consumption per capita of Nicaraguan households. This suggests the need for stronger public policies and more resources in order to adapt to the effect of climate change. Furthermore, the poverty reduction attainments reached since the 1990s could be jeopardized if this vulnerability persists.